Ways of pointing to artworks: a Wittgensteinian approach - Rubio Marco, Salvador (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2019)
The aim of P. Kivy’s recent De Gustibus: Arguing about Taste and Why We Do It (2015) is to answer to the very same question in terms of an emphasis on belief based on «phenomenological» (if not also ontological) «art-realism». Those who disagree on taste do so because they (explicitly or implicitly) see, in judgments relating to properties of artworks, the expression of beliefs, some of which are «true», and true in virtue of correctly reporting «facts» (non-aesthetic art-relevant facts, aesthetic art-relevant facts, or art value facts), and they try to convince others of what they think is «real» about art. Kivy follows the traces of this phenomenology of «beautiful» found in Hume’s work (and vs. Kant’s work). The main criticism is that it is actually possible to defend an alternative approach to understanding art in terms of «aspects» (an allegedly ‘anti-realist’ concept), so as to take account of rationality, disputes and the role of facts regarding judgments of taste. Kivy does not concede enough attention to the aesthetic experiences of seeing now what we were unable to see before (the «dawning» of an aspect), for example.